Nasal Chondrosarcoma of the Lower Lateral Cartilage - Tan, Hannah B. (Medicina (Kaunas), 2019)
Head and neck chondrosarcomas are incredibly rare with documented cases arising from skull base, maxilla, larynx, and nasal septum. We present the first reported case of chondrosarcoma arising from the lower lateral cartilage of the nose treated with surgical resection and primary reconstruction.